RETRACTION NOTICE : Developing G-Smartive (Getting Smart in Narrative) Multimedia as an Aid to Learn Reading of Narrative Text for Tenth Graders of Vocational High School - Putri Ika Ayundha Ningtyas (EDUCAFL : Journal of Education of English as Foreign Language, 2020)
This article entitled "Developing G-Smartive (Getting Smart in Narrative) Multimedia as an Aid to Learn Reading of Narrative Text for Tenth Graders of Vocational High School" (2020), authored by Putri Ika Ayunda Ningtyas, published in Volume 3, Issue 1. of Journal of Education of English as Foreign Language, pp.47-54 has been retracted. The Journal of Education of English as Foreign Language found the double publication in the article publishing due to article's content similarity published in https://educafl.ub.ac.id/index.php/educafl/article/view/166. One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited.  As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process